Torque Ripple Minimization of a Switched Reluctance Motor - Bilgiç, Mehmet Oruç; Özbulur, Veysel; Sabanovic, A. (My University, 1995)
This paper presents a simple technique to minimize torque ripple of a switched reluctance motor. The technique is based on the control of the sum of the square of the phase currents by using only two current sensors and analog multipliers. The simulation results and a proposed circuit are given. The advantages and its limitations of the proposed circuit are explained.
Keywords: Torque Ripple; Switched Reluctance Motor; Torque; Reluctance motors; Circuits; Reluctance machines; Inductors; Variable speed drives; Switching converters; Servomotors; Shape; Phase modulation